Single-step novel biosynthesis of silver nanoparticles: a potent and eco-friendly mosquitocides - Marimuthu Govindarajan, Kadarkarai Murugan, Kaliyan Veerakumar (Journal of Ecobiotechnology, 2016)
Mosquito-borne diseases like malaria, dengue, chikungunya, filariasis, and Japanese encephalitis cause thousands of deaths per year. Mosquito control is to enhance the health and quality of life of county residents and visitors through the reduction of mosquito populations. Mosquito control is of serious concern in developing countries like India due to the lack of general awareness, development of resistance, and socioeconomic reasons. Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. In view of the recently increased interest in developing plant origin insecticides as an alternative to chemical insecticide, In this research, we biosynthesized silver nanoparticles (Ag NP) using the Sida acuta leaf extract as reducing and stabilizing agent. The biosynthesis of Ag NP was confirmed analyzing the excitation of surface plasmon resonance using ultravioletâ€“visible (UVâ€“vis) spectrophotometry. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed the clustered and irregular shapes of Ag NP. The presence of silver was confirmed by energy dispersive X-ray (EDX) spectroscopy. Fourier transform infrared (FTIR) spectroscopy investigated the identity of secondary metabolites, which may also act as Ag NP capping agents. The acute toxicity of S.acuta leaf extract and biosynthesized Ag NP was evaluated against larvae of Aedes aegypti, Anopheles stephensi, and Culex quinquefasciatus. Compared to the leaf aqueous extract, biosynthesized Ag NP showed higher toxicity against Ae. aegypti, Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â An. stephensi, and Cx.quinquefasciatus with the LD50 values of 35.12, 39.53 and 41.44 Âµg/mL, respectively. This result suggests that the leaf extract have the potential to be used as an ideal eco-friendly approach for the control of vector mosquitoes.